ENTREPRENEURS, FINANCIERS, AND BOOM–BUST CYCLES. (22nd April 2016) - Kunieda, Takuma; Shibata, Akihisa
Abstract : In this paper, a dynamic general equilibrium model with infinitely lived entrepreneurs and financiers is developed to investigate a possible mechanism that explains business cycles and financial crises. The highest growth rate is achievable only if financiers coexist with entrepreneurs, given a certain extent of financial market imperfections. However, if financiers coexist with entrepreneurs, the economy is highly likely to face a financial crisis at certain parameter values. These two-sided implications of the coexistence of entrepreneurs and financiers explain why both instability and high growth are frequently observed in modern economies. Furthermore, our model can obtain countercyclical movements in total factor productivity growth that cannot be explained by the standard real business cycle theory but were observed in the Great Recession of 2007–2008.